Growth, Morphological and Genetic Variation of Azadlrachta Excelsa (Jack) Jacobs Genotypes - Abdul Hamid, Hazandy (2001)
A study was made on six seed sources of Azadirachta excelsa Jack) Jacobs at ages one and two years at two different locations, i.e. Rantau Panjang (Selangor) and Merchang (Terengganu) to determine the patterns of interand intra-specific variation in growth, genetic and morphological characteristics of this species. Measurements of survival, height, basal diameter (BD) and diameter breast height (DBH) were made on all trees at ages one and two years after planting in the field. Five characteristics of leaf morphology, i.e. leaf shape, leaf margin, leaf base, leaf angle and internode were also analysed for seed source variation. In addition, 19 enzyme systems were used to determine the genetic variation among seed sources using isozyme analysis. All the seed sources survived well during the first year with 91.25% in Rantau Panjang and 70.00% in Merchang but the survival reduced to 86.45% and 41.33% respectively during the second year. The mean height values ranged from 126.85 cm to 209.38 cm in Rantau Panjang and 49.76 cm to 72.19 cm in Merchang during the first year, and 212.83 cm to 367.07 cm in Rantau Panjang and 85.40 cm to 156.16 cm in Merchang during the second year. Whereas, the mean values of BD ranged from 2.04 em to 3.40 em in Rantau Panjang and 0.64 em to 0.87 em in Merchang during the first year, and 3.33 cm to 5.65 em in Rantau Panjang and 0.97 em to 1.54 em in Merchang during the second year. Meanwhile, the mean values of DBH for the first and second years ranged from 0.85 cm to 2.23 cm and 1.94 cm to 3.98 cm in Rantau Panjang respectively while in Merchang, the mean values of DBH ranged from 0.53 to 0.93 for second year.